2011
DOI: 10.1016/j.ajpath.2010.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke–Induced Pulmonary Inflammatory Responses Are Mediated by EGR-1/GGPPS/MAPK Signaling

Abstract: Early growth response 1 (EGR-1) contributes to the development of chronic obstructive pulmonary disease in the lungs of smokers by mediating pulmonary inflammatory responses, but the direct downstream genes of EGR-1 that regulate this process remain unknown. We show that a new EGR-1 target gene, geranylgeranyl diphosphate synthase (GGPPS), which controls protein prenylation, can regulate the proinflammatory function of EGR-1 by activating MAPK signaling. When C57BL/6 mice were exposed to cigarette smoke, EGR-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 56 publications
(59 reference statements)
2
34
0
Order By: Relevance
“…When we exposed the mice to cigarette smoke for 27 weeks, we found that EGR-1 and GGPPS appeared to be constantly activated and that they promoted inflammatory responses and tissue damage. 26 As a novel EGR-1 target gene, GGPPS may mediate the function of EGR-1 during cigarette smoke exposure by driving sustained ERK 1/2 activation. In addition, the transcription of several other EGR-1 target genes (eg, HO-1, 49 human IL-2, 12 IL-2 receptor, 14 Fas/CD95, 15 and intercellular adhesion molecule 1 16 ) may also be inhibited by the DnEGR-1 adenovirus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When we exposed the mice to cigarette smoke for 27 weeks, we found that EGR-1 and GGPPS appeared to be constantly activated and that they promoted inflammatory responses and tissue damage. 26 As a novel EGR-1 target gene, GGPPS may mediate the function of EGR-1 during cigarette smoke exposure by driving sustained ERK 1/2 activation. In addition, the transcription of several other EGR-1 target genes (eg, HO-1, 49 human IL-2, 12 IL-2 receptor, 14 Fas/CD95, 15 and intercellular adhesion molecule 1 16 ) may also be inhibited by the DnEGR-1 adenovirus.…”
Section: Discussionmentioning
confidence: 99%
“…Thus we have identified a novel feedback pathway that augments EGR-1-induced inflammatory responses in cultured cells and in a mouse model of pulmonary inflammation. 26 This study may provide additional insight into the complex processes that lead to cigarette smoke-related damage to respiratory tissues.…”
mentioning
confidence: 96%
“…Candidate genes are retrieved according to the information from the website (http://www.sabiosciences. com/Cytokines_Inflammation.php), BioCarta and KEGG pathways which are two common databases that provide displays of gene interactions for human cellular processes (http://cgap.nci.nih.gov/Pathways) and literatures (Shen et al, 2011;Yu et al, 2011;McMillan et al, 2011 ;Lee et al, 2012) commonly acknowledged as important inflammatory genes associated with smoking.…”
Section: Selection Of Candidate Genesmentioning
confidence: 99%
“…Furthermore, both Egr-1 and its target genes GGPPS and HO-1 were increasingly expressed in the lung from the cigarette smoke induced COPD mice. GGPPS is the enzyme that prenylates and activates Ras and re-activates the MAPK/Erk1/2, sequentially activates Egr-1 expression in a positive feedback way [23,24]. The constant activated Egr-1 by long-term smoke enhances the inflammation in pulmonary and over-activates the metalloprotease, eventually aggravates the impairment of lung tissue.…”
Section: The Ras Prenylation-and Cigarette Smoke-induced Pulmonary DImentioning
confidence: 99%